Pinning Control for the p53-Mdm2 Network Dynamics Regulated by p14ARF - Suarez, Oscar J.; Vega, Carlos J.; Sanchez, Edgar N.; González-Santiago, Ana E.; Rodríguez-Jorge, Otoniel; Alanis, Alma Y.; Chen, Guanrong; Hernandez-Vargas, Esteban A. (Frontiers in Physiology, 2020)
p53 regulates the cellular response to genotoxic damage and prevents carcinogenic events. Theoretical and experimental studies state that the p53-Mdm2 network constitutes the core module of regulatory interactions activated by cellular stress among a great variety of signaling pathways. In this paper, a strategy to control the p53-Mdm2 network regulated by p14ARF is developed, based on the pinning control technique, which consists into applying local feedback controllers to a small number of nodes (pinned ones) in the network. Pinned nodes are selected on the basis of their importance level in a topological hierarchy, degree of connectivity in the network, and the biological role they perform. In this paper, two cases are considered. For the first case, oscillatory pattern under gamma-radiation is recovered; afterward, as the second case, increased expression of p53 level is taken into account. For both cases, the control law is applied to p14ARF(pinned node), and overexpressed Mdm2-mediated p53 degradation condition is considered as initial behavior. The approach in this paper uses a computational algorithm, which opens an alternative path to understanding cellular responses to stress, doing it possible to model and control the gene regulatory network dynamics in two different biological contexts. As the main result of the proposed control technique, the two mentioned desired behaviors are obtained.